Time-Varying Mesh Compression Using an Extended Block Matching Algorithm - Seung-Ryong Han; Yamasaki, T.; Aizawa, K. (IEEE transactions on circuits and systems for video technology, 2007)
Time-varying mesh, which is attracting a lot of attention as a new multimedia representation method, is a sequence of 3-D models that are composed of vertices, edges, and some attribute components such as color. Among these components, vertices require large storage space. In conventional 2-D video compression algorithms, motion compensation (MC) using a block matching algorithm is frequently employed to reduce temporal redundancy between consecutive frames. However, there has been no such technology for 3-D time-varying mesh so far. Therefore, in this paper, we have developed an extended block matching algorithm (EBMA) to reduce the temporal redundancy of the geometry information in the time-varying mesh by extending the idea of the 2-D block matching algorithm to 3-D space. In our EBMA, a cubic block is used as a matching unit. MC in the 3-D space is achieved efficiently by matching the mean normal vectors calculated from partial surfaces in cubic blocks, which our experiments showed to be a suboptimal matching criterion. After MC, residuals are transformed by the discrete cosine transform, uniformly quantized, and then encoded. The extracted motion vectors are also entropy coded after differential pulse code modulation. As a result of our experiments, 10%-18% compression has been achieved.